The Trifecta of Sustainable Entrepreneurship: A Systematic Literature Review Study - Daniel Chang; Kristy Yeoh; Kouk Ping Jap (International Journal of Entrepreneurship and Sustainability Studies, 2023)
Several publications approach the subjects of sustainable entrepreneurship (SE). This study aims to explore the body of literature between 2017-2022 on sustainable entrepreneurship that is still evolving. Besides that, it aims to establish the research gaps and future research agenda to support the scholarly investigation of the subject matter. This study uses a systematic literature review as a scientific inquiry to uncover the richness and establish holistic perspectives on the sustainable entrepreneurship knowledge domain. This study results from 1,659 articles through Emerald and Scopus academic databases, supplemented with the Google Scholar search engine. Through the comprehensive inclusion and exclusion process with PRISMA 2000, only 42 documents were selected for the synthesis study. There are three critical findings uncovered. Firstly, discover Macro-Meso-Micro dimension’s underpinnings theory as the foundation to look at the holistic subject matter of sustainable entrepreneurship. Secondly, with the synthesis of 42 articles, eight thematic surfaced. Third is identifying a new emerging conceptual framework to understand sustainable entrepreneurship and its correlational impact within the Macro-Meso-Micro dimension. However, the proposed multiple research gaps and future agenda are within the emerging theme of sustainable entrepreneurship. It is a field that involves qualitative and quantitative inquiry, and it will bring new knowledge for academic development and support practitioner thirst to embrace sustainable entrepreneurship.